Souvenirs development related to cultural heritage: a thematic review - Zhu, Qiuxia; Rahman, Rizal; Alli, Hassan; Raja Ahmad Effendi, Raja Ahmad Azmeer (Mary Ann Liebert, 2023)
Previous souvenir research has generally supported the use of heritage arts and crafts as a design inspiration, which both arouses visitors’ interest in the destination and enhances the local cultural identity. The increasing concern about souvenirs and cultural heritage has led to a proliferation of studies on this topic. However, few review articles discuss their inevitable connection and the process of transforming cultural heritage resources into souvenirs. Therefore, this review aims to analyze the literature on souvenirs related to cultural heritage from 2018 to July 2022. A criterion for inclusion and exclusion is presented to search and screen articles from three leading databases (i.e., WOS, Mendeley, and Scopus). Ultimately, 27 articles meeting the eligibility criteria were selected for synthesis analysis. ATLAS.ti 9, as the analysis software, yielded quantitative results showing trends in research on cultural heritage-related souvenirs. At the same time, from the qualitative analysis emerged four main themes about the topic: (1) significance of souvenirs, (2) customer’s purchase intention, (3) transformation, and (4) sustainability. Finally, the findings are expected to be beneficial in addressing the relationship between souvenirs and cultural heritage and provide insights for future research and practice of cultural product sustainability.